The Use of Interrupted Case Studies to Enhance Critical Thinking Skills in Biology - Tracy K. White (American Society for Microbiology, 2009)
There has been a dramatic increase in the availability of case studies for use in the biology classroom, and perceptions of the effectiveness of case-study-based learning are overwhelmingly positive. Here we report the results of a study in which we evaluated the ability of interrupted case studies to improve critical thinking in the context of experimental design and the conventions of data interpretation. Students were assessed using further case studies designed to evaluate their ability to recognize and articulate problematic approaches to these elements of experimentation. Our work reveals that case studies have broad utility in the classroom. In addition to demonstrating a small but statistically significant increase in the number of students capable of critically evaluating selected aspects of experimental design, we also observed increased student engagement and documented widespread misconceptions regarding the conventions of data acquisition and analysis.